ARTIFICIAL INTELLIGENCE (AI) AND BLOCKCHAIN INTEGRATION: SYNERGIES, APPLICATIONS, AND FUTURE PROSPECTS - Ravikumar, Hemachandran; Ramachandran, Arumugam; Pandithurai, Pandiyarajan; Vasanthan; Poovan, Shanmugavelan (ShodhKosh: Journal of Visual and Performing Arts, 2025)
Two groundbreaking technologies transforming the scene of modern industry and government are blockchain and artificial intelligence (AI). Blockchain provides a distributed, unchangeable, safe ledger system for data exchange and transaction recording. AI, in the meantime, gives robots the capacity to examine data, identify trends, learn from mistakes, and make independent decisions. Combining these two technologies produces a symbiotic relationship whereby blockchain guarantees data trust and transparency, and artificial intelligence helps cognitive processing and dynamic automation. Their combined potential is investigated in this work using Blockchain-as-a-Service (BaaS), Blockchain-as-a-Cloud (BaaC), AI-enhanced smart contracts, and distributed autonomous systems. We evaluate present tools, investigate practical uses, and handle issues including scalability, computational expenses, and regulatory issues. These technologies are great assets to sectors including banking, supply chain, healthcare, and government since their combination shows an accuracy potential of over 90% in important uses.